Green Tea Consumption and Risk of Pancreatic Cancer: A Meta-analysis - Zeng, Jin-Long (Nutrients, 2014)
Emerging laboratory and animal studies indicate that green tea inhibits development and progression of pancreatic cancer, but evidence from epidemiologic studies appears inconsistent and inconclusive. A meta-analysis summarizing published case-control and cohort studies was performed to evaluate the association of green tea consumption with risk of pancreatic cancer. Pertinent studies were identified by a search of PubMed and EMBASE up to April 2014. A random-effects model was assigned to compute summary risk estimates. A total of three case-control studies and five prospective studies were included, comprising 2317 incident cases and 288209 subjects. Of them, three studies were from China and the reminders were conducted in Japan. Overall, neither high vs. low green consumption (odds ratio (OR) = 0.99, 95% confidence interval [CI] = 0.78–1.25), nor an increase in green tea consumption of two cups/day (OR = 0.95, 95% CI = 0.85–1.06) was associated with risk of pancreatic cancer. The null association persisted when the analysis was stratified by sex or restricted to non-smokers. In the stratification by study location, the summary OR for the studies from China and for those from Japan was 0.77 (95% CI = 0.60–0.99) and 1.21 (95% CI = 0.94–1.54), respectively (P for differences = 0.04). Cumulative epidemiologic evidence suggests that green tea consumption is not associated with pancreatic cancer.